2011
DOI: 10.1016/j.jempfin.2011.05.008
|View full text |Cite
|
Sign up to set email alerts
|

In- and out-of-sample specification analysis of spot rate models: Further evidence for the period 1982–2008

Abstract: We review and construct consistent in-sample specification and out-of-sample model selection tests on conditional distributions and predictive densities associated with continuous multifactor (possibly with jumps) and (non)linear discrete models of the short term interest rate. The results of our empirical analysis are used to carry out a "horserace" comparing discrete and continuous models across multiple sample periods, forecast horizons, and evaluation intervals. Our evaluation involves comparing models dur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 79 publications
0
2
0
Order By: Relevance
“…The empirical results demonstrated that the modified bias‐corrected estimators improved the out‐of‐sample forecasting performance of the LS estimator for almost all the selected interest rate series. There are numerous studies on interest rate and yield curve forecasting in the finance literature, including Byers and Nowman (1998); Duffee (2002); Nowman and Saltoglu (2003); Hong, Li, and Zhao (2004); Inci and Lu (2004); Diebold and Li (2006); Treepongkaruna (2006); Guidolin and Timmermann (2009); Cai and Swanson (2011); and de Rezende and Ferreira (2013). Our results contribute to the literature on interest rate forecasting.…”
Section: Introductionmentioning
confidence: 99%
“…The empirical results demonstrated that the modified bias‐corrected estimators improved the out‐of‐sample forecasting performance of the LS estimator for almost all the selected interest rate series. There are numerous studies on interest rate and yield curve forecasting in the finance literature, including Byers and Nowman (1998); Duffee (2002); Nowman and Saltoglu (2003); Hong, Li, and Zhao (2004); Inci and Lu (2004); Diebold and Li (2006); Treepongkaruna (2006); Guidolin and Timmermann (2009); Cai and Swanson (2011); and de Rezende and Ferreira (2013). Our results contribute to the literature on interest rate forecasting.…”
Section: Introductionmentioning
confidence: 99%
“…The mentioned models and the mentioned tests are popular in economics and finance". Some other recent applications of CHFs not stated in Nadarajah and Teimouri (2012) are: average rate claims with emphasis on catastrophe loss options (Bakshi and Madan, 2002); international cooperation, coalitions stability and free riding in a game of pollution control (Breton et al, 2006); oil price dynamics (Askari and Krichene, 2008); in-and out-ofsample specification analysis of spot rate models (Cai and Swanson, 2011); and, evaluation of European compound option prices (Griebsch, 2013).…”
mentioning
confidence: 99%